I survived the eruption of Mount St. Helens, 1980 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Incorporated, 2016)
On May 18, 1980, eleven-year-old Jessie Marlowe and her best friends, Eddie and Sam, are in a forest near Mount St. Helens when the months of wondering whether the volcano will erupt are finally answered--all three are badly burned, but it is up to Jessie to protect the boys as best she can and hope that somebody comes to rescue them.
Includes questions and answers about the eruption of Mount St. Helens and bibliographical information.
Keywords: Best friends -- Juvenile fiction; Survival -- Juvenile fiction; Volcanoes -- Washington (State) -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Survival -- Fiction; Volcanoes -- Fiction; Saint Helens, Mount (Wash.) -- Eruption, 1980 -- Juvenile fiction; Saint Helens, Mount (Wash.) -- Eruption, 1980 -- Fiction